Lincoln, Neb., Rev. Ordinances pt. 2, ch. 14, art. 26, § 17 (1895) - (:unkn) unknown (My University, 1895)
Prohibited the ability to keep, sell, or give away gun powder or gun cotton without the signed permission of the Fire Chiefs and the City Clerk. Penalty of twenty-five dollars.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER